The Ethics of Preventive War / [electronic resource] - Chatterjee, Deen K. (Cambridge : Cambridge University Press, 2013)
In this book, eleven leading theorists debate the normative challenges of preventive war through the lens of important public and political issues of war and peace in the twenty-first century. Their discussion covers complex and topical subjects including terrorism, the 'Bush doctrine' and the invasion of Iraq, Iran's nuclear capabilities, superpower unilateralism and international war tribunals. They examine the moral conundrum of preventive intervention and emphasize the need for a stronger and more effective international legal and political order and a corresponding re-evaluation of the normative status of international law. Together their essays form a challenging and timely volume that will be of interest to scholars in ethics and political philosophy, political theory, international relations, international law and peace studies and to general readers interested in the broader issues of peace and justice in the new world order.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Aggression (International law); Just war doctrine; Self-defense (International law); Preventive war